Psychology in Chile: Analysis of Its History, Present and Future [Psicología en Chile: Análisis de Su Historia, Presente y Futuro] - Vera-Villarroel, P (Pontificia Universidad Javeriana, 2015)
This paper present a review of the development and current state of Chilean psychology. In 1946 formally establishes the formation of psychologists in Chile; in 1959, it made official the Association of Psychologists of Chile and in 1968 the College of Psychologists of Chile was founded. This puts Chile in the first countries in the region in the formal development of the discipline. Currently, there are 139 training programs in psychology, taught in 49 universities. Added to that, a growing supply of master s and doctoral programs in psychology. With regard to the scientific development of the discipline shown a sustained increase in the number of published articles, noting that since 2011 has exceeded 100 items per year, although this production is linked to a few institutions and authors with high prominence. Additionally, a low collaboration between Chilean and Latin American researchers in studies and scientific productivity, despite sharing similar issues and problems observed. Regarding future challenges, it is necessary to increase systems quality assurance in pre and postgraduate courses, as well as the most influential psychologists of society.